Do right‐ventricular trabeculae gain energetic advantage from having a greater velocity of shortening?. (24th September 2017) - Pham, Toan; Han, June‐Chiew; Taberner, Andrew; Loiselle, Denis
Abstract : Key points: We designed a study to test whether velocity of shortening in right‐ventricular tissue preparations is greater than that of the left side under conditions mimicking those encountered by the heart in vivo . Our experiments allowed us to explore whether greater velocity of shortening results in any energetic advantage. We found that velocity of shortening was higher in the rat right‐ventricular trabeculae. These results at the tissue level seem paradoxical to the velocity of ventricular ejection at the organ level, and are not always in accord with shortening of unloaded cells. Despite greater velocity of shortening in right‐ventricular trabeculae, they neither gained nor lost advantage with respect to both mechanical efficiency and the heat generated during shortening. Abstract: Our study aimed to ascertain whether the interventricular difference of shortening velocity, reported for isolated cardiac tissues in vit ro, affects interventricular mechano‐energetic performance when tested under physiological conditions using a shortening protocol designed to mimic those in vivo . We isolated trabeculae from both ventricles of the rat, mounted them in a calorimeter, and performed experiments at 37°C and 5 Hz stimulus frequency to emulate conditions of the rat heart in vivo . Each trabecula was subjected to two experimental protocols: (i) isotonic work‐loop contractions at a variety of afterloads, and (ii) isometric contractions at a variety of preloads. Velocity of shortening was calculated from the former protocol during the isotonic shortening phase of the contraction. Simultaneous measurements of force–length work and heat output allowed calculation of mechanical efficiency. The shortening‐dependent thermal component was quantified from the difference in heat output between the two protocols. Our results show that both extent of shortening and velocity of shortening were higher in trabeculae from the right ventricle. Despite these differences, trabeculae from both ventricles developed the same stress, performed the same work, liberated the same amount of heat, and hence operated at the same mechanical efficiency. Shortening heat was also ventricle independent. The interventricular differences in velocity of shortening and extent of shortening of isolated trabeculae were not manifested in any index of energetics. These collective results underscore the absence of any mechano‐energetic advantage or disadvantage conferred on right‐ventricular trabeculae arising from their superior velocity of shortening. Key points: We designed a study to test whether velocity of shortening in right‐ventricular tissue preparations is greater than that of the left side under conditions mimicking those encountered by the heart in vivo . Our experiments allowed us to explore whether greater velocity of shortening results in any energetic advantage. We found that velocity of shortening was higher in the rat right‐ventricular trabeculae. These results at the tissue level seem paradoxical to the velocity of ventricular ejection at the organ level, and are not always in accord with shortening of unloaded cells. Despite greater velocity of shortening in right‐ventricular trabeculae, they neither gained nor lost advantage with respect to both mechanical efficiency and the heat generated during shortening.